2013
DOI: 10.1007/978-94-007-7006-5_31
|View full text |Cite
|
Sign up to set email alerts
|

Multi-layer Decentralized MPC of Large-scale Networked Systems

Abstract: In this chapter, a multi-layer decentralized model predictive control (ML-DMPC) approach is proposed and designed for its application to large-scale networked systems (LSNS). This approach is based on the periodic nature of the system disturbance and the availability of both static and dynamic models of the LSNS. Hence, the topology of the controller is structured in two layers. First, an upper layer is in charge of achieving the global objectives from a set O of control objectives given for the LSNS. This lay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 13 publications
0
18
0
Order By: Relevance
“…Distributed MPC has been studied for different applications including control and coordination of power systems [52,64] and urban traffic control [65]. Decentralized and distributed MPC strategies have also been studied in water related applications such as level control in tanks [66] and coordination in water supply networks [67,68,69]. A review of different distributed MPC configurations and future research directions in this field can be found in [70].…”
Section: Model Predictive Control (Mpc)mentioning
confidence: 99%
“…Distributed MPC has been studied for different applications including control and coordination of power systems [52,64] and urban traffic control [65]. Decentralized and distributed MPC strategies have also been studied in water related applications such as level control in tanks [66] and coordination in water supply networks [67,68,69]. A review of different distributed MPC configurations and future research directions in this field can be found in [70].…”
Section: Model Predictive Control (Mpc)mentioning
confidence: 99%
“…On the other hand, centralized and decentralized control approaches are not in the scope of this manuscript. However, comparisons and discussions in that sense over the Barcelona DWN case study have been already carried out [43], [44]. Table II summarizes the obtained control results in terms of performance (water and electrical cost) over four days of typical demand.…”
Section: A Results With the Barcelona Dwnmentioning
confidence: 99%
“…Some of these elements follow the description reported in [15] for flow networks, but will be included here for the proper completeness of the discussion.…”
Section: Control-oriented Modeling Methodologymentioning
confidence: 99%